1983
DOI: 10.1002/1097-0142(19830915)52:6<1105::aid-cncr2820520629>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prolonged intermittent therapy with combined 5-FU and methyl-CCNU following resection for gastric carcinoma. A veterans administration surgical oncology group report

Abstract: This prospective evaluation of 5‐fluorouracil (5‐FU) and methyl‐CCNU administered in combination to patients with surgery for histologically proved gastric adenocarcinoma is based upon 312 patients randomized between August 1974 and May 1980. Patients were stratified into three categories of resectability, (1) complete, (2) proven incomplete, and (3) nonresectable, prior to random treatment assignment to surgery alone or surgery followed by adjuvant chemotherapy. Drug therapy consisted of discrete 5‐day course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A smallscale randomized study found that adjuvant chemotherapy based on the semustine (Me-ccnU) and 5-FU regimen resulted in longer overall survival compared with surgery alone (22), although this result was not confirmed by a largescale phase III trial (23).…”
Section: Adjuvant Chemotherapy or Chemoradiotherapy After Surgerymentioning
confidence: 99%
“…A smallscale randomized study found that adjuvant chemotherapy based on the semustine (Me-ccnU) and 5-FU regimen resulted in longer overall survival compared with surgery alone (22), although this result was not confirmed by a largescale phase III trial (23).…”
Section: Adjuvant Chemotherapy or Chemoradiotherapy After Surgerymentioning
confidence: 99%
“…One study done by the Gastrointestinal Tumor Study Group using these drugs found a survival advantage [18]. Unfortunately, trials by the Veterans Surgical Oncology Group [19] and Gastric cancer remains a significant healthcare problem throughout the world and is usually diagnosed at a fairly advanced stage in the West. Despite complete resection of the primary tumor, most patients eventually experience a relapse and die of recurrent disease.…”
Section: Chemotherapy Adjuvant Trialsmentioning
confidence: 99%
“…In the reviewed papers important prognostic factors are not considered, like localisation of the primary tumour (Allum et al, 1989a;1989b;Harrisson et al, 1989;Nakajima et al, 1978;Koyama et al, 1986;Ochiai et al, 1983;Popiela et al, 1988;Allum et al, 1989c;GITSG, 1982), age (Coombes et al, 1990;Harrisson et al, 1989), and performance status or loss of weight (Higgins et al, 1983; Alcobendas et al, 1983; Coombes et al, 1990;Harrison et al, 1989;Tonnesen et al, 1988;Moertel et al, 1984;Hugier et al, 1980;Nakajima et al, 1980;Koyama et al, 1986;Maehara et al, 1990;Ochiai et al, 1983;Schlag, 1987;IGTSG, 1988).…”
mentioning
confidence: 99%
“…The majority of them gives no details on the procedure (Harrisson et al, 1989;Tonnesen et al, 1988;Moertel et al, 1984;Engstrom et al, 1985;Hugier et al, 1980;Nakajima et al, 1978;Nakajima et al, 1980;Maehara et al, 1990;Schlag, 1987;Lise et al, 1989;Allum et al, 1989c;Koyama et al, 1986;Higgins et al, 1983;Popiela et al, 1988;GITSG, 1982;Blake et al, 1981;Alcobendas et al, 1983) some lay down guidelines for surgical procedure (Coombes et al, 1990;Ochiai et al, 1983;Serlin et al, 1969;GITSG, 1982;IGTSG, 1988) or recommend a specific type of resection (Allum et al, 1989b). None had organised a pathological review of all operative specimens (Coombes et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation